A Special Issue on Nanomaterials for Electronic Device Applications - Yakuphanoğlu, Fahrettin (Amer Scientific Publishers, 2014)
[Abstract Not Available]
Keywords: Optical-Properties; Liquid-Crystals; Quantum Dots; Behavior; Films